Identifying Issues and Contexts: Obstacles for TPE Students in Designing Problem-Based Learning - Nurhamzah Nurhamzah; Asep Andi Rahman; Rikrik Nurdiansyah; Miftahul Fikri; Dindin Nasrudin; Zulmi Ramdani (PAEDAGOGIA, 2025)
Problem-Based Learning (PBL) is widely recognized as an effective approach to developing students' critical thinking and problem-solving skills. However, its implementation often encounters significant challenges, particularly in teachers’ ability to identify relevant contextual issues. This study investigates the perceptions and challenges faced by students in the Teacher Professional Education (TPE) Program in selecting and designing contextual issues for PBL. Using a sequential exploratory mixed-method design, the research began with a qualitative phase analyzing student assignments, followed by a quantitative phase involving questionnaires to assess perceptions and influencing factors. Results revealed that most TPE students have not yet fully developed the ability to select appropriate issues to serve as contexts in PBL. 90% of participants found it "Difficult" to identify relevant issues, while only 10% considered it "Easy." Among the factors contributing to these difficulties, limited knowledge of relevant issues (30%) was the most significant, followed by a lack of understanding of PBL concepts (23%) and difficulty connecting theory to practice (18%). Other barriers included limited access to resources (13%), time constraints (8%), and other minor reasons (8%). These findings emphasize the importance of structured and practical training programs to enhance teachers' competence in identifying contextual issues for PBL. The study concludes with recommendations for designing intensive professional development programs and highlights the need for further research with larger and more diverse samples to validate these findings.